Metode Pembelajaran Fiqih Dalam Memudahkan Pemahaman Hukum Islam - Zali, Muhammad (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Learning is a combination composed of human elements, materials, facilities, equipment and procedures that influence each other in achieving learning objectives. The methodology if fiqh learning is a method adopted by educators in conveying Islamic laws that relate to human life both in relation to God and those related to humans.